2023
DOI: 10.3892/etm.2023.11999
|View full text |Cite
|
Sign up to set email alerts
|

Proanthocyanidins: A novel approach to Henoch‑Schonlein purpura through balancing immunity and arresting oxidative stress via TLR4/MyD88/NF‑κB signaling pathway (Review)

Abstract: Henoch-Schonlein purpura (HSP), a recurrent and immunoglobulin (Ig)A-mediated vasculitis, presents not only as skin lesions but also as systemic involvement that can be life-threatening. Although the etiology of HSP remains unknown, immune imbalance and oxidative stress (OS) are primary contributors to its pathogenesis, alongside the abnormal activation of Toll-like receptor (TLR)/myeloid differentiation primary response gene 88 (MyD88)/nuclear factor-κB (NF-κB) pathway. TLRs, especially TLR4, stimulate downst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 129 publications
0
2
0
Order By: Relevance
“…Then TLR4, by binding to MyD88, excites downstream NF-κB signaling pathway to encourage inflammatory factors release and ROS production, further irritating inflammatory responses and OS occurrence. 30 , 58 Above molecular events in turn exacerbate vascular endothelial cells injury and vascular permeability, eventually lead to the onset of HSP. 45 , 57 , 59 These confirm the importance of TLR4/MyD88 /NF-κB in HSP pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then TLR4, by binding to MyD88, excites downstream NF-κB signaling pathway to encourage inflammatory factors release and ROS production, further irritating inflammatory responses and OS occurrence. 30 , 58 Above molecular events in turn exacerbate vascular endothelial cells injury and vascular permeability, eventually lead to the onset of HSP. 45 , 57 , 59 These confirm the importance of TLR4/MyD88 /NF-κB in HSP pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“… 11 , 28 , 29 Given that the functions of PCs and the pathogenesis of HSP, PCs would be a promising treatment for HSP. 30 However, reports about PCs treating HSP scarcely exist. In the previous study, we initially revealed that PCs obviously relieved the clinical and pathological lesions of HSP-like rats, decreased the levels of inflammatory factors, ROS and MDA, and increased those of CAT, SOD and GSH, possibly involving the attenuation of inflammatory reaction and oxidative damage (as a separate paper to publish).…”
Section: Introductionmentioning
confidence: 99%